Ład instytucjonalny podstawą konkurencyjności polskiego rolnictwa - Lechwar, Małgorzata (An Institutional Order as a Basis of Polish Agriculture Competitiveness, 2006)
The paper assumes that an institutional order plays an essential part in the building of Polish agriculture competitiveness. It shows that contemporary Polish and European economy gives rises to institutional strengthening of this sector of competitiveness. At the same time the paper emphasizes a weakness of an existing institutional system, which can make essential barrier of competitiveness creation - not only agriculture competitiveness, but also Polish agro-business competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 15-20